Penyuluhan Pencegahan dan Latihan pada Nyeri Punggung Bawah di Posyandu Lansia Sari Sehat - Yuliana Ratmawati; Young Ari Kusworo; Fiqi Widyawati (STIKes Ibnu Sina Ajibarang, 2025)
Low back pain refers to a syndrome with manifestations in the form of pain and uncomfortable complaints such as muscle tension or stiffness in the lower back area. Low back pain can be caused by various causes, including mechanical factors, disorders of tendons, ligaments, fascia, and muscles, and abnormal posture. Musculoskeletal lower back pain caused by mechanical factors can be related to work, hobbies, and daily activities. The age factor is also one of the risk factors for the incidence of low back pain. The Sari Sehat elderly posyandu is one of the posyandu whose elderly are active in various activities in the community. For this reason, it is necessary to increase knowledge about the prevention of low back pain and its exercises. In this case, physiotherapy has an important role in increasing the knowledge of the elderly about prevention and exercise in low back pain so that the elderly can avoid complaints of back pain. Approach Method: Prevention counseling and exercises on low back pain. Place and time: Sari Sehat Elderly Posyandu, Palur Mojolaban, Sukoharjo.